The Demand for Chinese Language Communication Skills among Restaurant Employees in Chiang Mai Province - Liang, Jialin; Yadan, Luo; ดิษยะไชยพงษ์, ธีรวีร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study: 1) the demand for Chinese language use among restaurant employees in Chiang Mai Province, and 2) a comparison of Chinese language use among restaurant employees in Chiang Mai Province. This study is quantitative research, utilizing questionnaires distributed to 260 restaurant employees in Chiang Mai Province, with the sample size calculated using the Taro Yamane formula. Basic data analysis was conducted using descriptive statistics, including frequency, percentage, mean, and standard deviation. Additionally, t-tests and F-tests (ANOVA) were employed to examine differences, with pairwise comparisons made using Scheffe's method.          The research found that 1) The overall demand for Chinese language use among restaurant employees in Chiang Mai Province, as well as in each individual aspect, was at a high level. The aspects were ranked from highest to lowest as follows: speaking, listening, writing, and reading.  2) A comparison of Chinese language use among restaurant employees in Chiang Mai Province showed that different genders did not exhibit differences in overall or individual aspects of Chinese language communication needs. However, age, education level, and monthly income significantly influenced the overall demand for Chinese language communication at a statistical significance level of 0.05